Avian Communities in Forest Patches of Mount Halimun-Salak National Park, Bogor - Widodo, Wahju; Istiadi, Yossa; Priatna, Dolly (Journal of Posthumanism, 2025)
Habitat fragmentation due to human activities has affected the existence of bird communities in conservation areas, including the Gunung Halimun-Salak National Park (TNGHS). This study aims to evaluate the structure of bird communities in three main forest patches (Purasari, Garehong, and Kendeng) as well as one fragmented open area in the TNGHS area. Data collection was carried out between March and September 2023 using the Index Point Abundance (IPA) method, and the data was analyzed with indices of diversity, dominance, and community similarity. A total of 81 species of birds with 1,531 individuals were successfully recorded. The Kendeng forest patch shows the highest level of diversity (H′ = 3.23; R = 8.98), while open areas recorded the lowest values (H′ = 2.67; R = 5.97). The dominant species include Pycnonotus aurigaster, Orthotomus sutorius, Collocalia linchi, and Lonchura leucogastroides. The Kruskal-Wallis analysis showed that there was no significant difference in the number of species between sites (P > 0.05). The highest similarity index was found between Kendeng and Garehong (69.42%). The results of this study confirm the importance of protecting forest patches in maintaining bird diversity and highlight the real threat of habitat fragmentation to avifauna communities.